KARAKTERISASI BIOPOLIMER DAUN TANAMAN BUNGA SEPATU (Hibiscus rosa-sinensis) DAN PENGGUNAANNYA SEBAGAI EDIBLE FILM DENGAN PENAMBAHAN GLISEROL SEBAGAI PLASTICIZER - , FAIZAH ANDARINI, Prof. Dr. Ir. Djagal Wiseso Marseno, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hibiscus rosa-sinensis (China rose) leaves have been known for its high biopolymer of polysaccharide content in a form of mucilage. Biopolymer of polysaccharide is one of the basic components in edible films making. However, the research about edible film made from the biopolymer from its leaves is never to be done. The aims of this study were to characterize biopolymer of Hibiscus rosa-sinensis leaves for chemical properties (methoxyl group, water, ash, protein, fat, and carbohydrate content) and to characterize edible films made from the biopolymer added with glycerol as plasticizer for physical (tensile strength, elongation, and solubility) and barrier properties (water vapor transmission rate). The biopolymer of the leaves were extracted by water, then precipitated by ethanol, dried, and crushed. Three concentrations of biopolymer (1%, 1.25%, dan 1.5% b/v) were used in edible films making, while the concentration of glycerol was the same in each formula (30% b/b biopolymer). Result showed that the yield of biopolymer extraction was 4.17% (b/b), or gave about 41.7 grams of yield per kg of fresh leaves. The biopolymer isolate contained methoxyl groups about 5.11%, 11.70% of ash, 9.13% of water, 11.89% of protein, 0.96% of fat, and 58.68% of carbohydrates (by difference). The reducing sugar was not detected in the biopolymer hydrolyzed by acid. It also showed that as the concentration of biopolymer isolate film increased